Deciphering the morpho-physiological and biochemical response of sunflower hybrids with the application of biochar and slow-release nitrogen fertilizers under drought stress for sustainable crop production - Hussain, Shabir; Khan, Mehrab; Altaf, Muhammad Tanveer; Shah, Muhammad Nadeem; Alfagham, Alanoud T. (Frontiers in Plant Science, 2025)
Agriculture problems like drought stress and improper fertilization like overuse of nitrogen fertilizers for maximum productivity are the problem responsible for low yield of crop and environmental pollution. Biochar and slow releasing nitrogen fertilizers (SRNF) application in agriculture are the sustainable practices being used for better crop nutrient management strategies, since the well-recognized environmental problem caused by overusing fertilizers. Biochar also used as tools for sustainable way alleviating drought stress. For this, two-year field study was planned with randomized complete block designed (RCBD) and was replicated three time. Treatments included the two irrigation conditions like normal irrigation (CK) and drought stress (DS), two biochar treatments like biochar (BC) and without biochar (WBC); and three application of SRNF like zinc-coated urea (ZCU), sulfur-coated urea (SCU) and non-coated simple urea (SU). Results revealed that drought stress significantly reduced plant height (20.7%), stem diameter (25.6%), and achene yield (25.9%), while increasing antioxidant activity. Biochar mitigated these effects, increasing plant height by 23.2% and achene yield by 12.0% under drought stress. Among SRNFs, ZCU was most effective, improving photosynthetic rate (18.5%), chlorophyll content (12.3%), and achene yield (19.6%) under drought conditions. The combination of biochar and ZCU improved soil health, water retention, and nutrient efficiency, leading to enhanced plant growth and yield. Statistical analysis confirmed significant differences among treatments.